whats Factors determinan on ROA Rural Bank Owned By Local Goverment in Indonesia? - Chandra, Dony; Hendrian, Hendrian; Pambelum, Yohanes Juni (International Journal of Applied Management and Business, 2023)
Purpose – This research conducted to determine the factors that affect profitability Rural Bank Owned by Local Government in Indonesia. As we know, the establishment of BUMD aims to make a profit, but unfortunately there are still BUMD’s that record losses in 2022, especially in Rural Banks. Therefore, researchers want to know what factors influence ROA of Rural Bank Owned by local Government in Indonesia. Methodology/approach – by using data panel regression analysis the researcher wanted to test the factors that affect on ROA of Rural Bank Owned by Local Government in Indonesia. The data was from 64 Rural Bank financial report in 2019 to 2022.   Findings – It The result is the factor that has a very positive effect on ROA is LDR, The next factor that has a significant and negative effect is BOPO, while other factor that have no effect on ROA in Rural Bank Owned by Local Govermen in Indonesia are CAR and NPL. Novelty/value –  So far, research has been conducted to examine what factors that influence profitability in Commercial Banks. In this research, we would like to present what factors affect ROA at Rural Bank Owned by Regency government in Indonesia from 2019 to 2022.